Caracterização botânica e geográfica do mel de Apis mellifera L. produzido no Território do Recôncavo da Bahia - Nascimento, Andreia Santos do (2011)
This work had the objective to categorize the pollen types occurring in samples of Apis mellifera honey produced in the region of the Recôncavo da Bahia, Brazil, thus contributing to the understanding of the regional melliferous flora and beekeeping plants of the State of Bahia, Brazil. A total of 70 honey samples were obtained with beekeepers in 17 counties of the Recôncavo da Bahia, during March 2009 to February 2010. Flowering plants were accessed in a radius of 1.500 m around the evaluated apiaries. Samples were evaluated in the Núcleo de Estudos dos Insetos from Universidade Federal do Recôncavo da Bahia in Cruz das Almas county, Bahia. Pollen analysis of the honey samples were performed by the acetolysis method followed by quantitative and qualitative analysis. One hundred and twelve pollen types were identified within 35 plant families. The most frequent pollen types within samples were Syagrus coronata, found in 94.12% of the samples followed by Mimosa arenosa and M. pudica, both found in 88.24% of the samples. There were observed 240 species belonging to 171 genera and 52 families. Asteraceae was the family with the greatest diversity of species, followed by Fabaceae, Malvaceae, Caesalpiniaceae and Mimosaceae. Our results demonstrated a significant contribution of Asteraceae, Fabaceae, Caesalpiniaceae and Mimosaceae as important species for beekeeping activities in the region of the Recôncavo da Bahia.